Two novel non-holostane type glycosides from the viscera of sea cucumber Apostichopus japonicus. Issue 4 (2nd April 2020) - Zhang, Xuan-Ming; Han, Li-Wen; Sheng, Wen-Long; Li, Xiao-Bin; Zhang, Shan-Shan; Guo, Jing-Lan; Lin, Hou-Wen; Liu, Ke-Chun
Abstract: Two novel glycosides, apostichoposide A1 (1 ) and B1 (2 ), were isolated from the viscera of Chinese sea cucumbers ( Apostichopus japonicus, Selenka) collected in the Bohai sea. Both the isolated glycosides were characterized by non-holostane type aglycones having 18(16)-lactone and 7(8)-double bond. Cytotoxic activities of the two compounds were evaluated against three human cancer cell lines. Compound 1 had adequate cytotoxic activity against MGC-803 and PC-3M cell lines. Our results indicated that glycosides present in A. japonicus viscera are an important high value resource for biotechnological applications. Graphical Abstract: